Occurrence of Toxic Biogenic Amines in Various Types of Soft and Hard Cheeses and Their Control by Bacillus polymyxa D05-1 - Marwa A. Saad; Hagar S. Abd-Rabou; Ebrahim Elkhtab; Ahmed M. Rayan; Ahmed Abdeen; Afaf Abdelkader; Samah F. Ibrahim; Heba Hussien (Fermentation, 2022)
Egyptian cheeses are considered an important part of the Egyptian diet. This study aimed to examine 60 random samples of different types of commercial cheeses in Egypt, including soft cheeses (Domiati and Tallaga) and hard cheeses (Cheddar and Ras). The samples were subjected to chemical and microbial examination. Biogenic amines (BAs) are nitrogenous compounds found in a variety of foods; their presence is undesirable and related to spoilage, and can result in toxicological effects in humans. Thus, BAs were determined by using a high-performance liquid chromatography (HPLC) analysis. Moreover, the ability of Bacillus polymyxa D05-1 to reduce levels of experimentally added biogenic amines during the manufacturing of Tallaga cheese was investigated. The obtained results revealed variations in the chemical composition between the investigated samples. Furthermore, many cheese samples contained high levels of BAs, including histamine, tyramine and putrescine. Domiati cheese had the highest levels of BAs, followed by Tallaga and Cheddar, whereas Ras cheese had the lowest levels. The existence of yeasts, molds, coliforms and the high levels of BAs in cheese samples indicate the unsanitary conditions in which they were made and stored. Furthermore, addition of B. polymyxa D05-1 during Tallaga cheese manufacturing resulted in a reduction in BA levels.